Application of Learning Models Gallery Walk on Material System Respiration for Improving Learning Outcomes - Muhammad Nur; Ayunisari Ayunisari; Andi Badli Rompegading (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research was to find out whether the application of the Gallery Walk learning model to the Respiratory System material could improve student learning outcomes in class XI IPA 3 UPT SMA Negeri 7 Wajo. While the results of the study showed that the results of the first cycle test in table 1. 22 students had completeness with a proportion of 62.90% while those who were still under the minimum completeness criteria were 13 students with a proportion of 37.1%. Students who complete the first cycle are in the 62.90% category while the results of the second cycle test are in table 2. It can be seen that as many as 30 students with a proportion of 85.70% experienced completeness, while the other 5 students with a proportion of 14.30% individually still below the minimum completeness criteria value. Students who complete learning in cycle II are in the high category with a proportion of 85.7. Thus the results of the second cycle test have been successful and in table 3. it can be seen the completeness of student learning in cycles I and II. Based on the results of the research that has been described, it can be concluded that the application of the Gallery Walk learning model can improve student learning outcomes in class XI IPA 3 UPT SMAN 7 Wajo in Biology subject.